A network analysis of anxiety and depression symptoms among Chinese nurses in the late stage of the COVID-19 pandemic - Peng, Pu; Chen, Qiongni; Liang, Mining; Liu, Yueheng; Chen, Shubao; Wang, Yunfei; Yang, Qian; Wang, Xin; Li, Manyun; Wang, Yingying; Hao, Yuzhu; He, Li; et al. (Frontiers in Public Health, 2022)
Background: Nurses are at high risk for depression and anxiety symptoms after the outbreak of the COVID-19 pandemic. We aimed to assess the network structure of anxiety and depression symptoms among Chinese nurses in the late stage of this pandemic. Method: A total of 6183 nurses were recruited across China from Oct 2020 to Apr 2021 through snowball sampling. We used Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder scale-7 (GAD-7) to assess depression and anxiety, respectively. We used the Ising model to estimate the network. The index “expected influence” and “bridge expected influence” were applied to determine the central symptoms and bridge symptoms of the anxiety-depression network. We tested the stability and accuracy of the network via the case-dropping procedure and nonparametric bootstrapping procedure. Result: The network had excellent stability and accuracy. Central symptoms included “restlessness”, “trouble relaxing”, “sad mood”, and “uncontrollable worry”. “Restlessness”, “nervous”, and “suicidal thoughts” served as bridge symptoms. Conclusion: Restlessness emerged as the strongest central and bridge symptom in the anxiety-depression network of nurses. Intervention on depression and anxiety symptoms in nurses should prioritize this symptom. Aa